2017
DOI: 10.1186/s12879-017-2449-y
|View full text |Cite
|
Sign up to set email alerts
|

Screening for tuberculosis in an urban shelter for homeless in Switzerland: a prospective study

Abstract: BackgroundWhereas high risk groups such as asylum seekers are systematically screened for active tuberculosis (TB) upon entry in Switzerland, this strategy does not apply to homeless persons despite a reported high risk. Geneva health and social authorities implemented an intersectoral project to screen for active TB in homeless persons. We aimed to assess acceptability of this program and prevalence of active TB in this group.MethodsThis prospective study targeted all homeless adults registering for shelter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
2
11
0
2
Order By: Relevance
“…A study conducted in Paris, France, among recent migrants consulting in a primary care medical centre dedicated to people living in precarious conditions has revealed that only 31% of eligible migrants underwent TB screening by chest radiography [7]. An alternative screening method based on a questionnaire has been proposed in Geneva, Switzerland, in the setting of homeless shelters [8]. We conducted a cross-sectional 1-day survey at a Marseille homeless shelter aiming to assess the feasibility of conducting such questionnaire-based screening program.…”
mentioning
confidence: 99%
“…A study conducted in Paris, France, among recent migrants consulting in a primary care medical centre dedicated to people living in precarious conditions has revealed that only 31% of eligible migrants underwent TB screening by chest radiography [7]. An alternative screening method based on a questionnaire has been proposed in Geneva, Switzerland, in the setting of homeless shelters [8]. We conducted a cross-sectional 1-day survey at a Marseille homeless shelter aiming to assess the feasibility of conducting such questionnaire-based screening program.…”
mentioning
confidence: 99%
“…In this cross-sectional 1-day survey, adult homeless people housed in shelters A and B in Marseille were recruited on a voluntary basis during three campaigns conducted in March, May, and December 2019. Participants were systematically asked to provide basic demographic information and information on their smoking habits, and to complete a questionnaire specially designed to identify patients at a high risk of APTB [ 6 ]. Mobile CXR were systematically performed on site at enrolment and analysed by a pneumonologist.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire is designed to identify patients at high risk of APTB, based on their country of origin, clinical data, history of TB, and contact with TB patients ( www.tb-screen.ch , version 4.3.1 updated 3 January 2018) [ 6 ]. The questionnaire comprised nine closed simple questions available in 32 differences languages (together with visual and audio formats) that takes a short time to complete.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have attempted to report coverage of screening programmes, which remains challenging to quantify in hard-to-reach groups due to the frequently mobile nature of these populations 48,57 . Acceptance and uptake of screening are also rarely reported, with uptake ranging from 14-87% in the absence of specific incentives 40,41,43,[58][59][60][61] . Uptake is likely to be better with mobile (rather than off-site) screening programmes, though evidence for specific strategies to improve uptake is currently limited.…”
Section: Coverage and Uptake Of Screeningmentioning
confidence: 99%